ADAR-deficiency perturbs the global splicing landscape in mouse tissues - Kapoor, Utkarsh; Jakobi, Tobias; Dieterich, Christoph (Genome research, 2020)
Adenosine-to-inosine RNA editing and pre-mRNA splicing largely occur cotranscriptionally and influence each other. Here, we use mice deficient in either one of the two editing enzymes ADAR (ADAR1) or ADARB1 (ADAR2) to determine the transcriptome-wide impact of RNA editing on splicing across different tissues. We find that ADAR has a 100× higher impact on splicing than ADARB1, although both enzymes target a similar number of substrates with a large common overlap. Consistently, differentially spliced regions frequently harbor ADAR editing sites. Moreover, catalytically dead ADAR also impacts splicing, demonstrating that RNA binding of ADAR affects splicing. In contrast, ADARB1 editing sites are found enriched 5′ of differentially spliced regions. Several of these ADARB1-mediated editing events change splice consensus sequences, therefore strongly influencing splicing of some mRNAs. A significant overlap between differentially edited and differentially spliced sites suggests evolutionary selection toward splicing being regulated by editing in a tissue-specific manner.
Gesehen am 04.11.2020